Uncontrolled blood pressure among hypertensive adults with rheumatoid arthritis in Saudi Arabia: A cross-sectional study - Almalki, Ziyad S.; AlOmari, Bedor Abdullah; Alshammari, Tahani; Alshlowi, Areej; Khan, Mohd Faiyaz; Hazazi, Ali; Alruwaily, Maha; Alsubaie, Sarah; Alanazi, Faten; Aldossary, Norah; Albahkali, Raseel (Medicine (Baltimore), 2022)
Despite the availability and advancement of diagnostic and treatments with demonstrated benefits in minimizing cardiovascular morbidity and mortality, hypertension control rates remain suboptimal. Therefore, this research aimed to determine the prevalence of uncontrolled BP in rheumatoid arthritis (RA) patients and understand all potential risk factors for uncontrolled BP.We conducted a cross-sectional study on RA patients in 2 rheumatology clinics in 2 public hospitals in Riyadh. Patients' information such as demographics, comorbidities, drug use, and other clinical data were captured through a review of medical records and supplemented by patient interviews. Multivariate logistic regression was utilized for the analysis to identify the significant factors of uncontrolled BP (systolic BP ≥140 mm Hg or diastolic BP ≥90 mm Hg).In total, 834 subjects with RA and concomitant BP were involved in this cross-sectional study. The prevalence of uncontrolled BP was found to be 31.65% among all the study population. Multivariate analysis showed that males, subjects above 60 years of age, and smokers had a distinctly higher occurrence of uncontrolled BP. Among the patients with comorbid conditions, those with obesity, hyperlipidemia, diabetes, anemia, cancer, and reflex or gastroesophageal reflux disease also showed a significantly higher risk of uncontrolled BP (P < .05).The rate of uncontrolled BP was found to be alarmingly high in the study population. Age, gender, smoking, diabetes, obesity, hyperlipidemia, cancer, gastroesophageal reflux disease, and osteoporosis are independently linked with lack of BP control.